2021
DOI: 10.1038/s41536-021-00128-0
|View full text |Cite
|
Sign up to set email alerts
|

Targets identified from exercised heart: killing multiple birds with one stone

Abstract: Cardiovascular diseases (CVDs) are a major cause of mortality worldwide, which are mainly driven by factors such as aging, sedentary lifestyle, and excess alcohol use. Exercise targets several molecules and protects hearts against many of these physiological and pathological stimuli. Accordingly, it is widely recognized as an effective therapeutic strategy for CVD. To investigate the molecular mechanism of exercise in cardiac protection, we identify and describe several crucial targets identified from exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 150 publications
0
23
0
Order By: Relevance
“…Increasing evidence indicates that targets identified in exercised animal hearts have the potential to mitigate cardiac injury in multiple ways. 176 Molecules that are regulated in exercised animal hearts may promote physiological hypertrophy of cardiomyocytes and may have the potential to enhance the expression of proliferation markers of cardiomyocytes and prevent cardiomyocyte apoptosis as well. 9 …”
Section: Functional Experiments To Determine Targets In Response To Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that targets identified in exercised animal hearts have the potential to mitigate cardiac injury in multiple ways. 176 Molecules that are regulated in exercised animal hearts may promote physiological hypertrophy of cardiomyocytes and may have the potential to enhance the expression of proliferation markers of cardiomyocytes and prevent cardiomyocyte apoptosis as well. 9 …”
Section: Functional Experiments To Determine Targets In Response To Exercisementioning
confidence: 99%
“… 92 , 98 , 175 , 179 A deep understanding of the functions and mechanisms of exercise-responsive molecules paves the way for identifying novel myocardial protective or therapeutic targets for CVDs. 8 , 137 , 176 …”
Section: Functional Experiments To Determine Targets In Response To Exercisementioning
confidence: 99%
“…Of these, physical activity is one of the most important because aerobic exercise (70–75% VO 2max ) makes the heart resistant to myocardial infarction in rats ( Alizadeh Pahavani et al, 2020 ). A scientific study of more than 3,000 people found that aerobic exercise reduced hospitalization due to heart failure as well as cardiovascular events ( Mediano et al, 2018 ; Wang et al, 2021 ). Other studies have shown that aerobic exercise (Equivalent to 70–75% VO 2max ) increases anti-apoptotic factors such as B-cell lymphoma 2 (Bcl-2) and decreases apoptotic factors such as BCL2 associated X (Bax) in the myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, understanding the mechanisms by which exercise induces physiological hypertrophy and cardioprotection will inform the development of exercise interventions and exercise-based therapeutics for the treatment of cardiovascular disease. 8 , 9 …”
mentioning
confidence: 99%